Los factores de riesgo psicosocial y su influencia en la accidentabilidad evaluados en una empresa contratista del sector minero - Guevara Terrones, Henry (2025)
This study was conducted at a contractor company in the mining sector. The aim was to find the correlation between psychosocial factors and accident rates. The CoPsoQistas21 questionnaire was used to identify the psychosocial factors, and the correlational analysis was carried out by applying Spearman’s Rho test. The test confirmed the hypothesis that there is statistical significance between psychosocial factors and accident rates. The influential psychosocial factors identified included psychological demands, such as speed and scheduling of activities, as well as emotional exhaustion, among others, and social support, which was dimensioned by autonomy, responsibility, and collaboration, among others. It was also found that the factor related to job insecurity regarding the future does not impact the occurrence of accidents.